Pollen Germination in Different Genotypes of Gladiolus - Poon, Tul Bahadur; Rao, TM; Aswath, C; Rajasekharan, PE; Kumar, DP (Nepal Journal of Science and Technology, 2011)
Fresh pollen of 16 promising genotypes of gladiolus was tested for their pollen viability. Modified cellophane method was employed to assess the pollen viability. Pollen germination media consisted of 15% sucrose supplemented with 300 ppm calcium nitrate, 200 ppm magnesium sulphate, 100 ppm potassium nitrate and 100 ppm boric acid. Highly significant variations were observed for percentage of pollen germination, non-germinated pollen and sterile pollen. The highest pollen germination (76.41%) was in genotype Hybrid selection 88-10-22, and did not differ significantly from Gladiolus callianthus (75.41%), Sapna (75.10 %), Hybrid selection 86-32-11, (73.28 %), Kum Kum (69.41%), Poonam (69.22 %), Hybrid selection 87-22-1 (67.87 %), Hybrid selection 87-1-1 (67.61 %), Psittacinus hybrid (64.64%) and Darshan (63.97%). The lowest non- germinated pollen (10.47%) was in genotype Gladiolus callianthus, and insignificantly followed by Hybrid selection 88-10-22 with 18.77 % and Hybrid selection 87-22-1 with 18.95 %. The lowest percentage of sterile pollen was noticed in genotype Sapna (2.82%) followed by Poonam with 4.00 % Hybrid selection 88-10-22 with 4.82% and Hybrid selection 82-11-27 with 5.22%. Key words: Gladiolus; germination; pollen DOI: 10.3126/njst.v11i0.4089 Nepal Journal of Science and Technology 11 (2010) 47-50